Formation of TiO2 Hollow Nanoparticles Studied by in Situ TEM - Štaffenová, Nikoleta; Bajtošová, Lucia; Chochoľaková, Elena; Hanuš, Jan; Cieslar, Miroslav (Manufacturing Technology Journal, 2025)
Hollow TiO₂ architectures are attractive for catalysis and sensing but typically produced by wet-chemical templating and sub-micron sizes. Here we demonstrate a dry, template-free route to nanoscale hollow shells by combining DC magnetron sputtering with in situ TEM heating. Heating to 900 °C produces sub-50 nm TiO₂ hollow shells with ~20 nm compact walls via oxidation-driven Kirkendall hollowing. The oxide evolves from amorphous at low temperature to anatase locally (~500 °C) and then to a rutile/brookite mixture by ~600 °C. The hollow architecture withstands a temperature of 900 °C without measurable sintering. Beam-off regions and ex-situ air annealing show the same hollowing and phase evolution, confirming a thermally driven, not beam-induced, transformation reproducible in air.
Keywords: Hollow TiO₂; Rutile/brookite; Magnetron sputtering; in situ TEM; Kirkendall effect